TEACHERS VS STUDENTS: PERCEPTIONS TOWARD THE SWITCH FROM OFFLINE TO ONLINE LEARNING AT THE PRIMARY SCHOOL LEVEL - Khilda Husnia Abidah (Premise: Journal of English Education and Applied Linguistics, 2022)
Online learning has been one of the best available options for coping with the teaching and learning process during the pandemic era. Understanding teachers' and students' perceptions of online learning has been an important and popular research topic. The focus of the current study is ascertaining whether the teachers and students can do the online teaching and learning process optimally. The subject of the study was 15 teachers and 52 primary students of SD Muhammadiyah 03 Tumpang who have faced online learning for almost two years. This study used a survey method with an online close-ended questionnaire to capture the perceptions of students and teachers on online learning implementation. The results indicated that the teachers and students perceived online learning negatively even though they agreed it was a suitable learning system during the pandemic. The study implies that online learning may positively or negatively impact students and teachers. However, it can be an alternative to learning over a long distance, and it is also one of the ways to define the technology to the teachers and students, especially in rural schools.